FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEIKUTSERTAAN MASYARAKAT DALAM KEPEMILIKAN JAMBAN SEHAT DI DESA SALAON TOBA KECAMATAN RONGGUR NIHUTA, SAMOSIR - Yenni Gustiani Tarigan; Anita Ratna Sari Gulo; Ivan Elizabeth Purba (NHM PRESS, 2023)
The use of latrines in various regions in Indonesia is still quite low, with 65.8% of the population using household latrines using their own latrines and 34.2% not owning latrines. This study aims to determine what factors are related to community participation in owning healthy latrines in Salaon Toba Village, Ronggur Nihuta District, Samosir Regency. This type of research is quantitative using analytical methods with a cross sectional research design. The population in this study were all heads of families or one in the family as well as being a sample of 65 heads of families. Primary data collection by distributing questionnaires. Data analysis was carried out in a bivariate manner to see the relationship between community participation in latrine ownership by using the Chi Square statistical test. The results of this study indicate that there is a significant relationship between knowledge (p-value= 0.000) and economic level (p-value=0.000) to owning a healthy latrine, while shame (p-value=0.759) and self-esteem (p-value=0.700) has no significant relationship to healthy latrine ownership. The conclusion is that good knowledge and family economy are related to the community building latrines, so it is suggested to the government to carry out counseling and create the community-led total sanitation (CLTS) programs so that people are free from open defecation.